(untitled) (Konturen, 2026)
This essay investigates the notion of imitation in Franz Kafka. It asks how notions of mimesis, mimicry, and metamorphosis inform a concept of realism in Kafka’s work which is irreducible to the aesthetic ideology of literary representation. For Kafka, mimesis is a corporeal process transforming the physiognomy of the writer, who is characterized by their facial expressions and gestures. Kafka’s prose, based on what he calls a ‘compulsion to imitate,’ oscillates like a “Vexierbild,” a picture puzzle, merging image and ground, identification and dissociation, reality and imagination. Its mimetic realism engenders grimacing texts, multi-stable images and riddles that leave the reader in a permanent state of confusion.